2005
DOI: 10.1007/s10493-004-5437-z
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Metarhizium anisopliae (Deuteromycetes) and permethrin to Ixodes scapularis (Acari: Ixodidae) nymphs

Abstract: Effectiveness of the entomopathogenic fungus Metarhizium anisopliae, for controlling nymphal Ixodes scapularis, was tested in laboratory and field trials. In the laboratory, M. anisopliae (Metschnikoff) Sorokin strain ESC1 was moderately pathogenic, with an LC50 of 10(7) spores/ml and induced 70% mortality at 10(9) spores/ml. In a field study, however, 10(9) spores/ml M. anisopliae did not effectively control questing I. scapularis nymphs, and significant differences were not detected in pre- and post-treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 63 publications
2
29
0
1
Order By: Relevance
“…solution containing Tween 80 at 0.1%, breaking the surface tension of the conidia and possibly improving the adhesion to tick cuticle. A synergistic effect was observed with the treatments of M. anisopliae combined with cypermethrin at 0.1%, causing >93% mortality in comparison with the separate treatments; similar results were reported by Hornbostel et al (2005) with the fungus and permethrin against I. scapularis. When the fungal treatments were mixed with D-limonene at 1%, mortality was not improved compared to either treatment used alone; mortality for the mixture did reach >90% at 1 Â 10 5 conidia/ ml and approached 100% at the three higher conidia levels.…”
Section: Discussionsupporting
confidence: 83%
“…solution containing Tween 80 at 0.1%, breaking the surface tension of the conidia and possibly improving the adhesion to tick cuticle. A synergistic effect was observed with the treatments of M. anisopliae combined with cypermethrin at 0.1%, causing >93% mortality in comparison with the separate treatments; similar results were reported by Hornbostel et al (2005) with the fungus and permethrin against I. scapularis. When the fungal treatments were mixed with D-limonene at 1%, mortality was not improved compared to either treatment used alone; mortality for the mixture did reach >90% at 1 Â 10 5 conidia/ ml and approached 100% at the three higher conidia levels.…”
Section: Discussionsupporting
confidence: 83%
“…in Ixodes persulcatus ticks in Russia, and Morozova et al (2002) found these pathogens to be distributed independently in I. persulcatus in western Siberia. Hornbostel et al (2005) found no differences in prevalence of B. burgdorferi s.s. in Ixodes scapularis ticks regardless of whether or not they were infected with the entomopathogenic fungus Metarhizium anisopliae. Swanson and Norris (2007) found that Borrelia burgdorferi s.s. and Rickettsia spp.…”
Section: Evidence Of Interactions Between Pathogens Within Tick Hostsmentioning
confidence: 64%
“…Identification of the significant transmission routes of B. burgdorferi ss is essential for effective management of the Lyme disease epidemic. In most cases, Lyme disease control strategies using B. burgdorferi ss vaccines or acaricides delivered mainly or exclusively to white-footed mice have resulted only in modest reductions in the number or infection prevalence of ticks (Dolan et al 2004;Tsao et al 2004;Hornbostel et al 2005;Ostfeld et al 2006b). Our results suggest that only limited success will accompany control strategies aimed at hosts if shrews are not included as targets for mitigation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is assumed that mice are primarily responsible for the propagation and prevalence of B. burgdorferi-infected ticks and thus Lyme disease risk. Many interventions and control strategies have focused on interrupting the transmission of B. burgdorferi ss from mice to ticks in order to reduce human exposure (Deblinger & Rimmer 1991;Dolan et al 2004;Tsao et al 2004;Hornbostel et al 2005). These interventions have resulted in only modest success in reducing B. burgdorferi ss infection prevalence in I. scapularis and thus minimal reductions in human Lyme disease risk.…”
Section: Introductionmentioning
confidence: 99%